THE SWOT ANALYSIS OF EFL LEARNERS’ ADAPTATION TO AI-BASED WRITING TOOLS IN ACADEMIC CONTEXTS - Muawwal Al As Ary; Misnawati Usman; Ahmad Rossydi; Ita Sarmita Samad; Sry Wahyuni (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
The purpose of this study was to analyze the adaptation of English as a Foreign Language (EFL) learners to AI-based writing tools in academic context. Although AI-based writing tools were progressively implemented into language education, limited research has explored how EFL learners interpreted and adapted to these tools. In particular, structured frameworks are infrequently applied to comprehensively analyze this perception. The study employed a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis to investigate EFL learners’ perceptions of AI writing tools such as Chat-GPT, Grammarly, or Quillbot. Data were gathered through semi-structured interviews involving 25 university EFL students. The findings uncovered that students conceived time efficiency and instant grammar feedback as key strengths. In contrast, excessive reliance and deficiency of deep academic understanding were seen as major weaknesses. Opportunities comprised enhanced writing confidence and facilitated idea generation and structured academic writing, while threats focus on diminished critical thinking and passive plagiarism. The results emphasized the demand for ethical pedagogical strategies to guide AI integration in language education.